FORMULATION AND CHARACTERIZATION OF SAMBILOTO EXTRACT ORALLY DISSOLVING FILMS: A DUAL MECHANISM FOR PROBIOTIC GROWTH AND ANTIBACTERIAL ACTION - MIKSUSANTI, MIKSUSANTI; APRIANI, ELSA FITRIA; AHMADI, ADIK; SHIYAN, SHAUM; WIJAYA, DINA PERMATA; RISANLI, VIO AGISTER (International Journal of Applied Pharmaceutics, 2023)
Objective: This study aimed to develop Orally Dissolving Films (ODFs) containing Sambiloto leaf extract and evaluate their effects on the growth of the probiotic bacterium Bifidobacterium longum (B. longum) and their antibacterial activity against Escherichia coli (E. coli). Methods: The ODFs were prepared using the solvent casting method with three concentrations: F1 (0.4%), F2 (0.6%), and F3 (0.8%). The growth of B. longum was assessed through the Total Plate Count method, while antibacterial activity was determined using the disc diffusion method. Results: F2 was chosen as the optimal formulation, characterized by a smooth texture, a pH of 6.240±0.026, thickness of 0.102±0.008 mm, weight of 0.059±0.002 mg, disintegration time of 16.633±0.822 seconds, folding endurance of 433.00±2.000 folds, and elongation of 22.250±1.372%. F2 significantly enhanced the growth of B. longum, yielding 2.43×10¹⁰ CFU/ml and a prebiotic index of 1.056 (p<0.05). Additionally, it demonstrated antibacterial activity with an inhibition zone diameter of 7.500±0.408 mm (p<0.05). Conclusion: This research highlights F2's potential as a nutraceutical product with both probiotic growth-enhancing and antibacterial properties.